Cefazolin versus anti-staphylococcal penicillins for treatment of methicillin-susceptible Staphylococcus aureus bacteraemia: a narrative review. (February 2018) - Loubet, P.; Burdet, C.; Vindrios, W.; Grall, N.; Wolff, M.; Yazdanpanah, Y.; Andremont, A.; Duval, X.; Lescure, F.-X.
Abstract: Background: Anti-staphylococcal penicillins (ASPs) are recommended as first-line agents in methicillin-susceptible Staphylococcus aureus (MSSA) bacteraemia. Concerns about their safety profile have contributed to the increased use of cefazolin. The comparative clinical effectiveness and safety profile of cefazolin versus ASPs for such infections remain unclear. Furthermore, uncertainty persists concerning the use of cefazolin due to controversies over its efficacy in deep MSSA infections and its possible negative ecological impact. Aims: The aim of this narrative review was to gather and balance available data on the efficacy and safety of cefazolin versus ASPs in the treatment of MSSA bacteraemia and to discuss the potential negative ecological impact of cefazolin. Sources: PubMed and EMBASE electronic databases were searched up to May 2017 to retrieve available studies on the topic. Contents: Although described in vitro and in experimental studies, the clinical relevance of the inoculum effect during cefazolin treatment of deep MSSA infections remains unclear. It appears that there is no significant difference in rate of relapse or mortality between ASPs and cefazolin for the treatment of MSSA bacteraemia but these results should be cautiously interpreted because of the several limitations of the available studies. Compared with cefazolin, there is more frequent discontinuation for adverse effects with ASP use, especially because of cutaneous and renal events. No study has evidenced any change in the gut microbiota after the use of cefazolin. Implications: Based on currently available studies, there are no data that enable a choice to be made of one antibiotic over the other except in patients with allergy or renal impairment. This review points out the need for future prospective studies and randomized controlled trials to better address these questions.